Evaluation of Standard Facilities and Infrastructure in Taman Belia Candi Kindergarten Semarang - K. S., Fenny Octaviana; Astuti, Henny Puji (BELIA: Early Childhood Education Papers, 2016)
Facilities and infrastructure were important tools of the education system. It was one of the eight national education standards which should be fulfilled. The availability of standard facilities was the main factor in improving the access services and education quality. This research was aimed to know the fulfillment of standard facilities and infrastructure based on the needs in Taman Belia Candi Kindergarten, Semarang. This research used evaluative method with descriptive qualitative approach supported by quantitative approach. Observation, interview, and documentation are utilized to gather the data collection. The validity of the data collection used sources triangulation and methodological triangulation. The data were analyzed by using techniques of data analysis which consists of three steps, included data reduction, display data, and conclusion. The result of the study showed that Taman Belia Candi Kindergarten, Semarang had fulfilled good and standard facilities based on Permendikbud No. 137 Tahun 2014. Taman Belia Candi Kindergarten, Semarang had infrastructures included area in 960m2, religion center, cooking sets, nature, role, beams, preparation, art, and gym, washbasin, library, outdoor playing place, children eating place, sandals place, multi purposes building, bathroom, the receptionist room, the administration room, the infirmary room, kitchen, warehouse, the teachers room, and the headmaster room. Taman Belia Candi Kindergarten, Semarang had tools included: class utensils, visual aid, the proponent alphabet, learning media, education playing tools, and central tools. The writer suggested to Taman Belia Candi Kindergarten, Semarang to maintain the quality of its facilities, in order to optimize and standardize the facilities based on the policy. In addition, Taman Belia Candi Kindergarten, Semarang should maintain its performance as the main superior kindergarten in Central Java which became the model to other kindergarten, and for policy makers so that more detail again in detailing policies in practice, in order to be more optimal.